2005
DOI: 10.1124/jpet.105.086736
|View full text |Cite
|
Sign up to set email alerts
|

Pyrimethamine (2,4-Diamino-5-p-chlorophenyl-6-ethylpyrimidine) Induces Apoptosis of Freshly Isolated Human T Lymphocytes, Bypassing CD95/Fas Molecule but Involving Its Intrinsic Pathway

Abstract: Pyrimethamine (2,4-diamino-5-p-chlorophenyl-6-ethyl-pyrimidine), a folic acid antagonist, may exert, in addition to antiprotozoan effects, immunomodulating activities, including induction of peripheral blood lymphocyte apoptosis. However, the molecular mechanisms underlying this proapoptotic activity remain to be elucidated. Here we show that pyrimethamine, used at a pharmacologically relevant concentration, induced per se apoptosis of activated lymphocytes via the activation of the caspase-8-and caspase-10-de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 32 publications
2
16
1
Order By: Relevance
“…In fact, pyrimethamine was able to induce upstream caspase activation (caspase-8), bypassing CD95/ Fas engagement, similarly to what we had previously observed in activated lymphocytes from a patient with a lymphoproliferative syndrome (16). This is noteworthy considering that the melanoma cell lines used in this study were shown to defy CD95-mediated apoptosis in vitro.…”
Section: Discussionsupporting
confidence: 59%
See 4 more Smart Citations
“…In fact, pyrimethamine was able to induce upstream caspase activation (caspase-8), bypassing CD95/ Fas engagement, similarly to what we had previously observed in activated lymphocytes from a patient with a lymphoproliferative syndrome (16). This is noteworthy considering that the melanoma cell lines used in this study were shown to defy CD95-mediated apoptosis in vitro.…”
Section: Discussionsupporting
confidence: 59%
“…According to what was observed in activated lymphocytes (16), this effect did not require CD95/Fas engagement, as shown by experiments performed with a specific mAb blocking CD95/Fas. However, we cannot rule out the possibility that a ligand-independent aggregation of the death receptor and a recruitment of death-inducing signaling complex could occur, as shown with some oxidizing agents or bile acids (33,34).…”
Section: Discussionmentioning
confidence: 80%
See 3 more Smart Citations